Internet of Things-Integrated Engine Cut-Off System for Monitoring Motorcycle Passenger Load Capacity Using Load Cell Sensors - Syahputra Fauzan; Gunawan; Raka Pratindy; Moch. Aziz Kurniawan (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – This study aimed to design and develop a motorcycle passenger load capacity monitoring prototype using load cell sensors integrated with an engine cut-off feature. The system was developed to detect loads exceeding the safe capacity threshold and activate a relay-based cut-off response under controlled prototype testing conditions. Methods – This research employed a Research and Development (R&D) approach involving hardware design, component assembly, sensor calibration, software programming, and functional testing. The system integrated a half-bridge load cell sensor, HX711 amplifier, ESP32 microcontroller, 20x4 I2C LCD display, relay module, GPS NEO-6M, step-down voltage converter, and web-based monitoring platform. The prototype was tested on a Honda BeAT 2013 motorcycle with a maximum safe load threshold of 123 kg. Findings – The load cell sensor accurately measured load variations from 40 kg to 140 kg, with readings closely matching reference load values. The engine cut-off system activated reliably when the load exceeded 123 kg for five consecutive seconds, with response times of 5 seconds at 130 kg and 140 kg. LCD and website displays showed synchronized values across all test loads. GPS testing produced an average deviation of 6.86 meters and an average accuracy of 86.29%. Research implications – The prototype demonstrates the technical feasibility of integrating load sensing, engine cut-off control, GPS tracking, and IoT-based monitoring for motorcycle overload prevention under controlled static testing conditions. Further dynamic-road testing, multi-sensor validation, IoT latency evaluation, and user-centered website testing are required before operational deployment. Originality – This study presents an integrated motorcycle safety prototype combining load cell sensing, HX711 amplification, ESP32 control, relay-based engine cut-off, LCD display, GPS tracking, and real-time website monitoring.